Predictors of Visual Functional Outcome Following Treatment for Cavernous Sinus Meningioma. (16th November 2020) - Fatima, Nida; Ding, Victoria; Han, Summer; Chang, Steven D; Meola, Antonio
Abstract: INTRODUCTION: Cavernous sinus meningioma (CSM) can affect the visual function and require expeditious treatment to prevent permanent visual loss. METHODS: Consecutive patients with CSM presented at an academic tertiary care hospital from 2000 to 2018 were identified through retrospective chart review. Visual outcomes-visual eye deficit (VED), optic disc (OD) appearance, intraocular pressure (IOP), and extraocular movement (EOM)-were assessed before and after treatment for CSM. VED with visual acuity (VA) ≤ 20/200 and visual field defect (VFD) ≥ -11 dB, pale OD appearance in the ipsilateral or contralateral eye, increased ipsilateral IOP, and/or EOM restriction. Multivariable logistic regression was used to evaluate the associations between pre-treatment visual functional assessment and post-treatment visual outcomes. RESULTS: The study cohort included 44 patients (73% female; median age 55 years), with a median clinical follow-up of 14 months. Ipsilateral VED improved, remained stable or worsened respectively in 0%, 33.4% and 66.6% of the patients after STR only, in 52.6%, 31.6% and 15.8% after STR with radiation treatment, in 28.5%, 43.0% and 28.5% after GTR alone, and in 56.3%, 43.7% and 0% after radiation treatment (SRS/SRT) alone. In multivariable analyses adjusting for age, tumor volume and treatment modality, initial poor VED (OR:10.1, 95%CI: 1.05-97.2, P  = .04) and pale OD appearance (OR:21.1, 95%CI: 1.6-270.5, P  = .02) were associated with post-treatment poor ipsilateral VED. Similarly, pale initial OD appearance (OR:15.7, 95%CI: 1.3-199.0, P  = .03), poor initial VED (OR:21.7, 95%CI: 1.2-398.6, P  = .03), and IOP higher in the ipsilateral eye (OR:55.3, 95%CI: 1.7-173.9, P  = .02) were associated with post-treatment pale ipsilateral OD appearance. Furthermore, higher initial ipsilateral IOP (OR:35.9, 95%CI: 3.3-400.5, P  = .004) was indicative of higher post-treatment IOP in the ipsilateral eye. Finally, restricted initial EOM was indicative of restricted post-treatment EOM (OR:20.6, 95%CI: 18.7-77.0, P  = .02). CONCLUSION: Pre-treatment visual functional assessment predicts visual outcome in patients with CSM and can be used to identify patients at greater risk for vision loss.